Molecular characterization of Arcobacter butzleri isolates from poultry in rural Ghana - Zautner, Andreas E.; Riedel, Thomas; Bunk, Boyke; Spröer, Cathrin; Boahen, Kennedy G.; Akenten, Charity Wiafe; Dreyer, Annika; Färber, Jacqueline; Kaasch, Achim J.; Overmann, Jörg; May, Jürgen; Dekker, Denise (Frontiers in Cellular and Infection Microbiology, 2023)
In recent years, Arcobacter butzleri has gained clinical significance as an emerging diarrheagenic pathogen associated with poultry and water reservoirs. The full clinical significance of Arcobacter remains rather speculative due to variable virulence and antibiotic susceptibility of individual strains. The aims of the present study were (i) to identify antibiotic resistance genes (ARGs) in the genome sequences of two multidrug-resistant A. butzleri isolates, (ii) to use multilocus-sequence typing (MLST) to generate a guiding phylogeny of A. butzleri isolates collected in Kumasi, Ghana, (iii) to examine the distribution of ARGs in the test cohort, and (iv) to assess the strain’s virulence and possible antibiotic treatment options for arcobacteriosis based on the genome sequences and the ARG distribution. A total of 48 A. butzleri isolates obtained from poultry were included in the analysis. These isolates were genotyped by MLST and the antibiotic susceptibilities of isolates to ampicillin, ciprofloxacin, tetracycline, gentamicin, and erythromycin were tested by disk diffusion. Whole genome sequence data of two multidrug-resistant (MDR) A. butzleri isolates were obtained by a combination of single-molecule real-time (SMRT) and Illumina sequencing technology. A total of 14 ARGs were identified in the two generated genome sequences. For all 48 isolates, the frequency of these 14 ARGs was investigated by PCR or amplicon sequencing. With 44 different sequence types found among 48 isolates, strains were phylogenetically heterogeneous. Four of 48 isolates showed an ARG constellation indicating a multidrug-resistant phenotype. The virulence genes in the two A. butzleri genomes showed that the species might be characterized by a somewhat lower virulence as Campylobacter species. The phenotypic susceptibility data combined with the distribution of the particular ARGs especially oxa-464 and the T81I point mutation of the quinolone resistance determining region (QRDR) in a significant percentage of isolates indicated that macrolides and tetracycline can be recommended for calculated antibiotic treatment of arcobacteriosis in Ghana, but not ampicillin and quinolones.